PENERAPAN BLUE OCEAN STRATEGY PADA TRANS STUDIO BALI PT. CHAIRUL TANJUNG CORPORA - Meyta Nurul Aini; Lina Auliana; Muhammad Rizal (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
This study aimed to evaluate BOS implementation, further with Covid-19 existence, particularly to examine BOS implementation showed three good characteristics or not, and company's response to Covid-19, concerning adoption barriers indicator. This study used qualitative method, employed in-depth interviews and questionnaires data collection to consumers and nonconsumers taken in October 2020. Four Actions Framework, ERRC Grid Scheme, and former studies brainstorming were used to analyze industrial competition factors, which were then analyzed using orthogonal varimax rotation factor to generate value curve. The results indicated company's value curve did not meet BOS's good characteristics, as reflected by high-value curve in first major competition factors, as well as lack of conditions adjustment during Covid-19. The managerial implication implied that it raised further questions whether market share and company profitability reflected investment or offered excess supply, as well as it urged the company to consider adjusting to conditions quickly. Keywords: Bali indoor theme park, blue ocean strategy, four action framework, ERRC grid scheme, varimax orthogonal factor rotation